Evaluating the Impact of Aggregate Size and Sediment Type on Clogging and Permeability of Pervious Concrete - Prahara, Eduardi; Suwondo, Riza; Christopher, Christopher (Engineering, Technology & Applied Science Research, 2025)
Pervious Concrete (PC) is increasingly being used in sustainable drainage systems owing to its ability to manage stormwater. However, sediment accumulation can clog pores and reduce their permeability. This study investigates the effect of various sediment types, sand, clay, gravel, and oil, on the permeability of pervious concrete samples with three different aggregate size ranges: 12.5–19.1 mm, 9.5–12.5 mm, and 4.75–9.5 mm. The concrete samples were subjected to sediment loads ranging from 0 g to 100 g, and the permeability was measured after each sediment addition. The objective was to assess the impact of sediment type and quantity on permeability reduction, and to evaluate the role of aggregate size in resisting clogging. The results demonstrate that larger aggregates maintained higher permeability and were less affected by sediment accumulation, whereas smaller aggregates experienced significant clogging and rapid permeability loss. Oil had the least impact on the permeability, whereas gravel and sand caused the greatest reduction. Permeability stabilisation occurred after sediment accumulation reached 60–70 g for all samples. These findings highlight the importance of aggregate size selection in pervious concrete designs to enhance long-term performance and resistance to clogging. Larger aggregates from 12.5 to 19.1 mm were shown to be the most effective in maintaining permeability, even under sediment load.